Build up of soil phosphorus in coffee plantations of Karnataka overthree decades - J.S. Nagaraja, P. Shiva Prasad; M. Violet D’ Souza, S.A.Nadafand (Journal of Plantation Crops, 2017)
Karnataka is the largest coffee producing State in India contributing 72.3 per cent of the total production of the country. Arabica Coffee is being cultivated in Karnatakain an area of 1.1 lakh ha and Robusta coffee in 1.2 lakh ha. Coffee growing soils are deep, friable, rich in organic matter, high in potassium content, well drained and slightly acidic in reaction. These soils contain large quantities of aluminium and iron oxides. Hence, phosphorus (P) availability in the Indian coffee growing soils is a constraint as the aluminium and iron oxides fix the appliedphosphorus. Soil testing laboratories(STLs) of Coffee Board are rendering advisory service to the growers based on soil analysis and classify the data into low, medium and high category. In order to know the impact of the lime and fertilizer management on the soil available P status of the coffee growing soils of Karnataka, the soil-P data were compiled and classified into different categories for the 3 districts, viz., Chikmagalur, Hassan and Kodagu for a period from 1980- 81 to 2015-16. The decade-wise data set on soil available phosphorus so obtained was analyzed and the changes occurred over a period of time were assessed.The results indicated that over a period of thirty six years clear cut shift has taken place from low to high category in the available P status of soils cropped to coffee. About 50per cent of the samples were low during 1980s while this has reduced to 42 per cent during 1990s and further reduced to 23per cent during 2016. On the other hand the percentage of samples under high category has gradually increased from 24 to 51.